Teams Games Tournament (TGT) Cooperative Learning Model in Learning Personification Figures of Speech - Anis Safira, Rahmadhani; Sukardi (Jurnal Penelitian dan Pengembangan Pendidikan, 2024)
Currently, many teachers still need to pay more attention to conducive learning activities. Teachers tend to use a student-centered learning model so that students feel bored while learning. Based on this, this research aims to analyze the effectiveness of the Teams Games Tournament (TGT) cooperative learning model in personification learning in fourth-grade elementary school. This type of research is experimental research. In this research, the design used was Nonequivalent Control Group Design. The population of this study was 42 fourth-grade elementary school students. The research sample was determined using the cluster random sampling technique. The methods used to collect data are tests, interviews, observation, documentation, and questionnaires. The technique used to analyze data is inferential statistical analysis. The research results, namely the t-test results, show differences in students' ability to understand personification figures of speech after being treated with the effective Teams Games Tournament learning model. The results of the N-gain test showed an increase in the average pretest and posttest scores for the experimental and control classes. It was concluded that the Teams Games Tournament Learning Model can improve student learning outcomes in learning personification figures of speech. This research implies that the application of TGT can improve student learning outcomes.